Neutralizing Their Involvement: Sex Traffickers' Discourse Techniques. (January 2014) - Copley, Lauren
This article seeks to extend the sex trafficking literature by addressing the knowledge gap surrounding sex traffickers. In addition, this analysis broadens Antonopoulos and Winterdyk's (2005) analysis by contending that sex traffickers in various sociohistorical contexts use neutralizations based on the intersectional vulnerabilities of their victims. An examination of the sociocultural influences on traffickers' use of techniques of neutralization contributes to a deeper understanding of sex trafficking and its cultural and social bases. This is essential to combating the practice as effective countermeasures must address the motivations, cultural constructions, and exploitation of intersectional identities that support sex trafficking.